Influence of vitamin C or/and L-methionine on hyperglycaemia, hyperlipidaemia and hematological alterations in alloxan-induced diabetes in rats - Abd El-Ghffar, Eman Ali; Barakat, Alaa; Shehata, Safa Mohamed (Progress in Nutrition, 2018)
Background: Here, we assessed the possible therapeutic potential of vitamin C or/and L-methionine on some biochemical and hematological alterations in alloxan-induced diabetes in rats. Diabetes was induced by single intraperitoneal (100 mg/kg b.w, i.p) dose of alloxan monohydrate solution. The animals were randomly grouped into five as follows: the normal control group, diabetic control group, diabetic treated with vitamin C (Vit C) group, diabetic treated with L-methionine (L-Meth) group, diabetic treated with Vit C and L-Meth group. The regimens were given once daily for four weeks. Significant disturbances in glucose, glycated hemoglobin, lipid profiles, prothrombin time (PT), partial thromboplastin time (PTT), some hematological and oxidant/antioxidant parameters was observed in diabetic control rats. Only the combination of Vit C and L-Meth had the most beneficial effect on hyperglycemia, dyslipidemia, abnormal coagulation indices and oxidative stress in alloxan-induced diabetes in rats. From the present data, we concluded that Vit C and L-Meth in combination may have therapeutic effects against the risks of the metabolic syndrome and coronary artery diseases and could improve the health of rats with diabetes mellitus.